The Impact of Local Revenue Growth and SME Credit Financing on GDP Expansion in Palu City, 2011-2022 - Marcella Chrysan Parengkuan; Failur Rahman (Golden Ratio of Data in Summary, 2024)
Local Original Revenue is part of the financial resources of local governments and has a major contribution to increasing Gross Domestic Product (GDP). This means that the higher the PAD obtained from the local government, the higher the value of the region's GDP. Efforts to increase PAD continue to increase and are balanced by its very dynamic growth compared to the amount of other banking loans. The purpose of this study was to see the effect of PAD development (X1), SME Credit Financing (X2) on the growth of Palu City GDP (Y). The type of data used in this study is secondary data obtained from the official website of the DJPK of the Ministry of Finance and the Central Bureau of Statistics. The research approach used is a quantitative approach to answer the hypothesis. The results of this study indicate that there is a significant effect between SME credit financing and PAD development. Then in this case, the growth of SMEs is measured by the total output obtained. As with the testing of the second hypothesis, it also results in the statement that there is a growth in SME GDP that has a close relationship with economic growth.